2021
DOI: 10.3390/ijms22136713
|View full text |Cite
|
Sign up to set email alerts
|

NEUROD1 Is Required for the Early α and β Endocrine Differentiation in the Pancreas

Abstract: Diabetes is a metabolic disease that involves the death or dysfunction of the insulin-secreting β cells in the pancreas. Consequently, most diabetes research is aimed at understanding the molecular and cellular bases of pancreatic development, islet formation, β-cell survival, and insulin secretion. Complex interactions of signaling pathways and transcription factor networks regulate the specification, growth, and differentiation of cell types in the developing pancreas. Many of the same regulators continue to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
14
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 46 publications
(89 reference statements)
7
14
0
4
Order By: Relevance
“…The terminal definitive differentiation into β mature cell identity is achieved by the final activation of pivotal transcription factors, such as NEUROD1, NKX2.2, NKX6, PAX4/6, PDX-1, MAFA, FOXA2, and MNX1 [ 343 , 344 ]. NEUROD1 (also known as BETA2) is a basic helix-loop-helix (bHLH) transcription factor, which is crucial for pancreatic development and is essential for the maturation and differentiation of β cells and insulin production [ 345 ]. NEUROD1, together with PDX-1, ISL1, and MAFA, are key transcription factors regulating insulin synthesis in pancreatic β cells in response to blood glucose [ 346 ].…”
Section: Mex Mir Signaling and Functional Immaturity Of β Cellsmentioning
confidence: 99%
“…The terminal definitive differentiation into β mature cell identity is achieved by the final activation of pivotal transcription factors, such as NEUROD1, NKX2.2, NKX6, PAX4/6, PDX-1, MAFA, FOXA2, and MNX1 [ 343 , 344 ]. NEUROD1 (also known as BETA2) is a basic helix-loop-helix (bHLH) transcription factor, which is crucial for pancreatic development and is essential for the maturation and differentiation of β cells and insulin production [ 345 ]. NEUROD1, together with PDX-1, ISL1, and MAFA, are key transcription factors regulating insulin synthesis in pancreatic β cells in response to blood glucose [ 346 ].…”
Section: Mex Mir Signaling and Functional Immaturity Of β Cellsmentioning
confidence: 99%
“…Synapse related proteins (n=44) included members of the synaptotagmin ( SYT4, 5, 7, 13, 14 ), and glutamate receptor ( GRIA2,3 ) families (Table S3, Tab 2), many of which are reported to be important for pancreatic endocrine cell function e.g., SYT4 (Huang et al, 2018) and SYT13 (Bakhti et al, 2021; Tarquis-Medina et al, 2021), whilst the function of others in this context is not currently known e.g., FRRS1L and NSG1 . Alpha and beta cell co-enriched genes included several encoding for transcription factors involved in islet cell specification, e.g., NKX2-2 , (Churchill et al, 2017), NEUROD1 (Bohuslavova et al, 2021), RFX6 (Soyer et al, 2010), INSM1 (Liang et al, 2021), PAX6 (Hart et al, 2013) and MYT1 (Wang et al, 2007), as well as those with no currently reported function in these cell types, e.g., CELF3 and MYT1L one could speculate such genes likely have a role in neuroendocrine cell function. 91 genes had predicted alpha cell-enrichment, including GCG, TTR and KCNH6 (Figure 3 B, left side); all of which are involved in glucose homeostasis (Noguchi and Huising, 2019; Su et al, 2012; Yang et al, 2018), and other genes with, as yet, no described function in this cell type e.g., SMIM24, CALY and C5orf38 (Figure 3 B, left side).…”
Section: Resultsmentioning
confidence: 99%
“…The focus of this study was to determine the requirements for NEUROD1 in the early neuronal development of the inner ear and processes that are affected by Neurod1 elimination (Figure 11). NEUROD1, a bHLH transcription factor, is an essential factor for the lineage commitment and differentiation in various developmental systems, including gastrointestinal cells (Cherry et al, 2011), pancreas (Romer et al, 2019;Bohuslavova et al, 2021), brain (Miyata et al, 1999;Liu et al, 2000b;Hevner et al, 2006), and neurosensory organs (Liu et al, 2000a;Cherry et al, 2011). The main function of NEUROD1 in neurogenesis and the promotion of neuronal fate is supported by its ability to reprogram other somatic cells into neurons.…”
Section: Discussionmentioning
confidence: 99%